The Influence of Nurse Manager's Transformational Leadership Style on Nurse's Medication Safety Dimediation Performance in Intention Room of Private Hospital in Pekanbaru - Andika Eka Putra; Siti Dyah Handayani; Nuryakin Nuryakin (Budapest International Research and Critics University, 2023)
The purpose of this study was to analyze the effect of the nurse manager's transformational leadership style on performance and medication safety.Respondents in this study aremedical staff working in a private hospital Pekanbaru.The samples used were 96 respondents with quantitative methods using SEM and Smart PLS, with a sampling techniqueconveniencesampling. Hypothesis testing using SEM-Partial Least Square; test the validity and reliability using confirmatory factors, cronbach's alpha and composite reliability. The results of this study indicate that the transformational leadership style of nurse managers has a positive and significant effect on performance and medication safety, performance has a positive and significant effect on medication safety and mediation performance has a positive and significant effect on nurse manager transformational leadership style on medication safety.